The Impact of HbA1C on Postoperative Complications Following Orthopaedic Surgeries to the Foot and Ankle: A Systematic Review - Jacek Parylo MB ChB, BSc (hons); Erika Pond; Paula McQuail MB BCh, BAO, MCh, FRCSI; Basil Budair MBBS, MSc, FRCS (Tr & Orth) (Foot & Ankle Orthopaedics, 2024)
Category: Ankle; Midfoot/Forefoot Introduction/Purpose: Type 2 diabetes mellitus (T2DM) is one of the most prevalent chronic conditions worldwide, with estimates that the number of diabetic patients worldwide will increase by 51% by 2045. Orthopaedic patients with poorly controlled T2DM and its associations, including peripheral vascular disease (PVD) and peripheral neuropathy (PN), are shown to be at risk of poorer functional outcomes and increased complication rates. The growing prevalence of T2DM makes it of huge clinical importance. It is crucial to understand how to identify and mitigate as much risk as is feasible in this population when considering foot and ankle surgery. Foot and ankle surgery is particularly fraught with difficulty given the predilection T2DM has for the foot in the development of Charcot neuroarthropathy on top of other complications. Methods: PubMed, Embase, Medline, Ovid, Cochrane library, and Trip medical database were searched to identify studies concerning postoperative complications and their relationship to pre-operative HbA1C measurements following foot and ankle surgeries. Studies containing data for amputations or drainage for existing diabetic foot ulcers were excluded, as results for surgical site infections (SSI) may be more likely for pre-existing ulcers. Patient characteristic data; intra-operative data; and post-operative complication data was collected. A specific focus was given to collecting data regarding pre-operative HbA1c values. Results: 2506 articles were highlighted on literature search. 29 full-text articles were accessible and read for inclusion. Of these, 14 full-text articles were included in the review. The following number of studies observed relationships between HbA1C and various complication types: 9 for SSI; 6 for bone healing complications; 1 for risk of amputation following major non-ulcerated Charcot reconstruction; 3 for re-operation; and 4 for nonspecific complications. Overall, higher HbA1C values were significantly associated with greater risk of SSI development; although 3 studies identified no significant correlations. No clear overall correlation could be found between higher HbA1c and bone healing complications, or nonspecific post-operative complications. Interestingly, data indicated that PN and PVD were at times better predictors of post-operative complications than isolated HbA1c values. Conclusion: In most cases, higher pre-operative HbA1C values, typically above 7-8%, predisposed patients to the development of SSI. Data regarding bone healing complications and re-operation was less clear. No clear HbA1c threshold was identified due to literature paucity. In some studies, the presence of PVD and PN predicted higher complication rates. Focussed attention should be given to T2DM from a foot and ankle perspective to determine the threshold for safer surgery. Further attention must also be given to the complication rates associated with PVD and PN alongside HbA1C, as this appears to be an important surrogate marker associated with complication rates.